Case Report: Complete and Fast Recovery From Severe COVID-19 in a Pemphigus Patient Treated With Rituximab - Sinagra, Jo Linda; Vedovelli, Claudio; Binazzi, Raffaella; Salemme, Adele; Moro, Francesco; Mazzanti, Cinzia; Didona, Biagio; Di Zenzo, Giovanni (Frontiers in Immunology, 2021)
COVID-19 is characterized by a severe pulmonary disease due to severe acute respiratory syndrome (SARS)-CoV-2 infection. For clinicians involved in the management of patients with chronic autoimmune diseases the risk linked to the conditions itself and to drug-induced immunosuppression during the COVID-19 pandemic is a major topic. Pemphigus is a rare autoimmune blistering disease (AIBD) of the skin and mucous membranes caused by autoantibodies to desmosomal components, desmoglein 1 and 3. Among immunosuppressant therapies, rituximab (RTX) is considered a highly effective treatment with a favorable safety profile, but it induces a prolonged B-cell depletion that can lead to higher susceptibility to infections. For this reason, concerns about its use during the pandemic have been raised. We describe a case of a pemphigus patient in which RTX-induced B cell depletion led to the severe inflammatory phase, whereas corticosteroid treatment allowed a favorable outcome. .